ТУКЛИ ЭРВАНИ КЎЧАТ УСУЛИДА ЕТИШТИРИШНИНГ ИҚТИСОДИЙ САМАРАДОРЛИГИ - Дустиёров Меҳрож Дилшодович (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This study examines the propagation techniques and agrobiological performance of Aerva lanata L. in the Shakhrisabz and Muborak districts (2022–2024). Direct sowing and seedling methods were tested under 70×20 cm and 70×30 cm schemes with different pruning treatments. Seedling cultivation ensured higher biomass and seed yield than direct sowing. Pruning increased branching, number of inflorescences, and productivity. The species showed stable adaptation (70 points) in both regions, confirming its suitability for cultivation in the Kashkadarya conditions